2021
DOI: 10.1155/2021/2491489
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dynamic, Mechanical, and Thermal Properties of Calotropis procera Particle‐Reinforced PLA Biocomposites

Abstract: The thermal behavior of the biodegradable Calotropis procera (CP) particle-reinforced polylactic acid (PLA) biocomposites was investigated. The injection molding process was used to make the composites, and the CP particle weight percentage was varied during the process (0%, 5%, 10%, 15%, and 20%). The melt flow index, heat deflection temperature, Vicat softening point, and the thermal properties of the composites were determined using dynamic mechanical testing. The results were analyzed and compared to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The tensile strength dropped significantly when 60% of the MRDCF was reinforced with PLA. This phenomenon might be due to the high content of fibers which may subsequently influence the mechanical properties of the composites [ 65 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Islam et al [ 174 ] found a Young’s modulus of 10.9 GPa and a tensile strength of 82.9 MPa in alkali-treated industrial hemp fiber (optimum loading of 30 wt %)-reinforced PLA composites.…”
Section: Pla-based Green Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength dropped significantly when 60% of the MRDCF was reinforced with PLA. This phenomenon might be due to the high content of fibers which may subsequently influence the mechanical properties of the composites [ 65 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Islam et al [ 174 ] found a Young’s modulus of 10.9 GPa and a tensile strength of 82.9 MPa in alkali-treated industrial hemp fiber (optimum loading of 30 wt %)-reinforced PLA composites.…”
Section: Pla-based Green Compositesmentioning
confidence: 99%
“…Numerous studies concentrate on the finished properties of composites but frequently neglect to discuss their processing and limitations due to their rheological behavior. While many researchers have focused on identifying the rheological behavior of traditional wood polymer composites based on well-defined commercial wood flour [ 165 , 166 , 167 , 168 ], the rheology of composites based on waste lignocellulosic materials with a variety of chemical structures and additional low-molecular products that might be emitted during melt processing is still inadequate. It should be noted that the addition of fillers typically rises the thermoplastic composites viscosity and reduces their processability [ 181 ].…”
Section: Pla-based Green Compositesmentioning
confidence: 99%
“…The transition temperatures of the composites decreased to lower temperatures due to the addition of the alumina particles and their plasticizing effects. The displaced peaks of the composites from pure PLA are owing to the increased flexibility of the composites (Yoganandam et al , 2021). The tan δ indicates the ratio of energy lost v/s energy stored in a loading cycle.…”
Section: Resultsmentioning
confidence: 99%
“…e peak HC emissions were 45 ppm for W20Bu5D75, 49 ppm for standard diesel, 48 ppm for WME20, and 42 ppm for W20Bu10D70 at the crest load. °C combustion, and lower calorific value of the standard diesel could be the prevailing reasons for indicating the trend for the samples of watermelon with additive n-butanol indorses lower HC emission [34][35][36]. e CO 2 emissions were 5% for W20Bu5D75, 5.19% for standard diesel, 5.23% for WME20, and 4.7% for W20Bu10D70 at the crest load.…”
Section: Brake Specific Fuel Consumptionmentioning
confidence: 87%